Gallien in Spätantike und Frühmittelalter Kulturgeschichte einer Region - Diefenbach, Steffen; Müller, Gernot Michael (Millennium-Studien / Millennium Studies, 2013)
The period from the 5th to the 7th century AD was characterised by far-reaching structural changes that affected the entire west of the Roman Empire. This process used to be regarded by scholars aspart of the dissolution of Roman order, but in current discussions it is nowexamined more critically. The contributions to this volume of conference papers combine approaches from history and literature studies in order to review the changing forms and fields of the establishment of collective identities, and to analyse them in their mutual relationships.